Electronic and thermoelectric properties of Nd-doped Ce-filled skutterudites. Issue 7 (4th February 2022) - Limbu, Nihal; Ram, Mahesh; Joshi, Himanshu; Saxena, Atul; Shankar, Amit
Abstract : The rattling of the central cage atom introduces strong phonon scattering that leads to reduced lattice thermal conductivity ( K L ) in the doped alloys and effectively enhances the dimensionless figure of merit ( ZT ). Abstract : The electronic and thermoelectric properties of Nd-doped Ce-filled skutterudites (CeFe4 P12, CeFe4 As12, and CeOs4 P12 ) were explored using full-potential linearized augmented plane waves (FP-LAPW). The exchange–correlation between the electrons was treated with the generalized gradient approximation of Perdew–Burke–Ernzerhof (PBE) and the Coulomb repulsion term ( U ) between the electrons for the highly correlated system was also considered. The energy band structures revealed the semiconducting nature with energy gaps of 0.42 eV, 0.25 eV and 0.22 eV for CeFe4 P12, CeFe4 As12, and CeOs4 P12, respectively. The phonon dispersion curve displayed the forbidden gap between the optical and acoustic modes in CeFe4 P12 and CeOs4 P12 . The analysis of n-type and p-type doping on pure alloys suggest enhanced thermoelectric behavior in p-type doping on pure alloys and hence the addition of Nd at the central cage atomic site generates flat and dense bands at E F and also opens an optical band gap in doped CeOs4 P12 . Moreover, the Nd atom introduces strong phonon scattering and hence reduces the lattice thermal conductivity ( K L ) substantially from 6.79 W m −1 K −1 to 3.47 W m −1 K −1 for CeFe4 P12, 3.63 W m −1 K −1 to 1.97 W m −1 K −1 for CeFe4 As12 and 6.43 W m −1 K −1 to 2.58 W m −1 K −1 for CeOs4 P12 at room temperature. A considerably amplified figure of merit has been observed for the doped sample materials with the highest value of 0.72 at 800 K for doped CeFe4 P12 with the highest Seebeck coefficient of 215.51 μV K −1 .